Integration of Green Innovation in Default Risk Management with Altman's Z"-Score and ZMIJEWSKI'S Zm-Score - Jemitra Jemitra; Buddi Wibowo (Eduvest - Journal of Universal Studies, 2025)
This study analyzes the effect of green innovation on the default risk of non-financial companies in Indonesia and China during the period 2018–2024. Both countries were selected because they have banking-based financial systems but face different environmental challenges. Default risk is measured using a combined accounting-based approach, namely Altman's Z”-Score, and Zmijewski's ZM-Score. The estimation results using the Fixed Effect Model show that in aggregate, green innovation has no significant relationship with default risk. However, when analyzed per country, the effect of green innovation is proven to be significant and negative on default risk in companies in China, while in Indonesia the relationship is not statistically significant. These findings indicate that the effectiveness of green innovation as a financial risk mitigation strategy is greatly influenced by institutional readiness and national policies. This study provides important insights for policymakers and market players in developing countries regarding the importance of supporting the green innovation ecosystem to strengthen financial stability.